Pain Symptomatology and Management in Pediatric Ehlers–Danlos Syndrome: A Review - Estée C. H. Feldman; Daniel P. Hivick; P. Maxwell Slepian; Susan T. Tran; Pradeep Chopra; Rachel Neff Greenley (Children, 2020)
Ehlers–Danlos syndromes (EDS) are a group of connective tissue disorders that manifest with hyperextensibility of joints and skin, and general tissue fragility. While not a major criterion for clinical diagnosis, pain is a frequently endorsed symptom across subtypes of EDS. As such, the present review aims to summarize research to date on pain characteristics and management, and the relationship between such pain symptomatology and quality of life in pediatric EDS. Characteristics of pain, including theorized etiology, relative intensity and extent of pain are described, as well as descriptions of frequently endorsed pain sites (musculoskeletal, and non-musculoskeletal). Interventions related to the management of musculoskeletal (e.g., pharmaceutical intervention, physical therapy) and non-musculoskeletal pain (e.g., pharmaceutical and psychological interventions) are discussed, highlighting the need for additional research related to pediatric pain management in the context of hypermobility syndromes. In addition, the relationship between pain in pediatric EDS and quality of life is described. Finally, limitations of literature to date are described and recommendations for future lines of research are outlined.